The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1475-2875-11-38
|View full text |Cite
|
Sign up to set email alerts
|

High IFN-gamma and TNF production by peripheral NK cells of Colombian patients with different clinical presentation of Plasmodium falciparum

Abstract: BackgroundIn Colombia, Plasmodium falciparum infection rarely results in severe disease or mortality compared to infections in African populations. During natural infection NK cells exhibit a cytolytic effect and regulate dendritic cells, macrophages, neutrophils as well as affect antigen specific T and B cell responses. To characterize the NK cells in P. falciparum infected patients of a highly endemic region of Colombia, the degree of NK proliferation and production of IFN gamma and TNF production in these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
14
1
Order By: Relevance
“…While NK cell blood proportions did not differ in acutely infected versus follow-up patients, these cells were strongly activated in severe malaria patients and in the Py mouse model, in line with prior in vitro reports [6466]. Likewise and as also suggested before [67], a slight decrease in the blood proportion of CD8 + and CD4 + T cells was observed in severe malaria patients and both subsets of T lymphocytes underwent robust activation, proliferation and differentiation.…”
Section: Discussionsupporting
confidence: 87%
“…While NK cell blood proportions did not differ in acutely infected versus follow-up patients, these cells were strongly activated in severe malaria patients and in the Py mouse model, in line with prior in vitro reports [6466]. Likewise and as also suggested before [67], a slight decrease in the blood proportion of CD8 + and CD4 + T cells was observed in severe malaria patients and both subsets of T lymphocytes underwent robust activation, proliferation and differentiation.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to the results of our study, NK cells appear to play an important role in the evolution of malaria [16]. Studies reveal that NK cells are among the first cells to respond to Plasmodium falciparum by producing IFN-gamma demonstrated by in vitro and in vivo studies [17]. These cells increase particularly in number [18].…”
Section: Discussioncontrasting
confidence: 99%
“…These cells increase particularly in number [18]. This role of NK has also been emphasized by several authors during simple [17] and severe manifestations of malaria [16][17][18][19]. However, studies of the dynamics of NK cells activity in patients with malaria have revealed heterogeneous results, particularly in individuals infected with P. falciparum [17].…”
Section: Discussionmentioning
confidence: 95%
“…5). Studies suggest that IFN-γ is produced by NK cells in malaria patients (20) and during in vitro culture with iRBCs (13). However, the role of IFN-γ in the antimalaria response is poorly understood.…”
Section: Discussionmentioning
confidence: 99%